Talking Hands - Stylianou-Lambert, Theopisti; Stefani, Elisavet; Nicolaou, Polina; Given, Michael (My University, 2024)
“Talking Hands” examines the experiences and stories of residents of Episkopi village in Cyprus whose lives were interwoven with archaeological work. Even though Episkopi residents were involved in archaeological excavations conducted by Cypriot and foreign missions since the beginnings of Cypriot archaeology in the 19th century, their thoughts and experiences have been omitted from official archaeological narratives. They usually remain unnamed and their work unacknowledged. Especially during colonial times, archaeological workers were considered the “hands” of archaeology; mindless manual workers not important enough to mention or document. To give voice to the “hands” of archaeology we decided to conduct an oral history and photography project titled “Talking Hands”. Since the stories of workers cannot be found in archaeological records and publications, we needed to talk directly to people who were involved in archaeological excavations or knew people who were. In 2022 and 2023, we talked to eleven participants, between the ages of 65 and 87, who were recruited through word of mouth. Most of our participants worked at archaeological excavations as seasonal workers, supporting staff for various expeditions, guards, or specialized technicians.
Χέρια Που Μιλούν
Keywords: archaeology; workers; photography; oral history